Total oxidisable precursor assay towards selective detection of PFAS in AFFF. (15th December 2021) - Al Amin, Md; Luo, Yunlong; Nolan, Annette; Robinson, Fiona; Niu, Junfeng; Warner, Scott; Liu, Yanju; Dharmarajan, Raja; Mallavarapu, Megharaj; Naidu, Ravi; Fang, Cheng
Abstract: Total oxidisable precursor assay (TOP assay) can degrade and convert "unknown" per- and polyfluoroalkyl substances (PFAS) to detectable PFAS. However, the detailed degradation pathway is still not known, particularly when the TOP assay is applied to analyse complex samples such as aqueous film-forming foam (AFFF). To gain insights into the pathway and the effectiveness of the TOP assay, several "known" compounds are first tested as controls, including sodium dodecyl benzene sulphate (SDBS), perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS). Secondly, the test is expanded to several PFAS precursors such as 6:2 fluorotelomer sulfonate (6:2 FTS), 8:2 fluorotelomer sulfonate (8:2 FTS), and a cationic surfactant N-ethyl-N-(2-hydroxyethyl) perfluorooctyl sulfonamide (EtFOSE). Thirdly, the TOP assay is used to test "unknown" PFAS samples that have been previously used as AFFF in Australia. The degradation products are monitored, to compare the mass balance and propose the degradation pathway. While HPLC-MS/MS is typically employed to detect the individual TOP assay products, most of which are perfluoroalkyl carboxylic acids (PFCA), an app-based smartphone sensor can also provide semi-quantitative results as a sum. Overall, the results indicate the effectiveness of the TOP assay to assess the presence of PFAS precursors in the AFFF samples, with some variations in the end products. Recommendations for enhancement of the TOP assay are also provided. Graphical abstract: Image 1 Highlights: Insights on TOP assay using blank control, negative control, positive control and PFAS precursors. FTS as indicator to suggest the TOP assay efficiency. Variation on the end products, particularly for real sample such as AFFF. Enhancement of TOP assay recommended. Semi-quantitative test achieved by an app-based smartphone sensor, with help D-LPE to remove background.